Witness interview strategy for critical incidents (WISCI). Issue 4 (14th June 2018) - Smith, Kevin; Milne, Becky
Abstract : Purpose: High-profile critical incidents involving multiple witnesses, particularly terrorist attacks, have increased over the years. The purpose of this paper is to describe the components of a witness interview strategy for this type of investigation. Central to these cases is a need for a triage system which deals with a large number of witness/victim interviews that must be conducted fast time. Design/methodology/approach: This paper was developed based on the experience of the authors who provide practical advice and support to these types of investigations and a dialogue with police interview advisers involved in developing this type of strategy. Findings: A witness interview strategy for critical incidents involving multiple witnesses should be set within a framework that covers initial contact with the witnesses, the interview process and post-interview processes. Practical implications: It is important that a witness interview strategy is developed for any critical incident involving multiple witnesses to ensure that what could otherwise be a chaotic process is effectively managed. Originality/value: No other papers have been published that consider the development of witness interview-strategies for multiple-witnesses in critical incidents.